PERANCANGAN GAME PENJUALAN PADA PT. ALOE VERA INDONESIA DENGAN RPG MAKER VX ACE - Maximilianus Maximilianus; Desi Arisandi (Fakultas Teknologi Informasi Universitas Tarumanagara, 2016)
“Struggle of Reason” is a Business-Simulation Game that tells the story of a young man named Eddy. This game is developed using RPG Maker VX Ace as the game engine. Player will be play as Eddy and follow the story of his life to pay off his father debts. In this game player will follow the story lines over the game, after 6 months running in the game, the player will be taken to the ending. The testing conducted using blackbox method, alpha testing and beta testing through surveys. The test results managed to give an overview of the information system to the layman as well as honing business experience.